Analysis of the Serum Peptidomics Profile for Cats With Sarcomeric Gene Mutation and Hypertrophic Cardiomyopathy - Sukumolanan, Pratch; Phanakrop, Narumon; Thaisakun, Siriwan; Roytrakul, Sittiruk; Petchdee, Soontaree (Frontiers in Veterinary Science, 2021)
Abstract Background: Hypertrophic cardiomyopathy (HCM) has a complex phenotype that is partly explained by genetic variants related to this disease. The serum peptidome profile is a promising approach to define clinically relevant biomarkers. This study aimed to classify peptide patterns in serum samples between cats with sarcomeric gene mutations and normal cats. Materials and methods: In the total serum samples from 31 cats, several essential proteins were identified by peptidomics analysis. The 5,946 peptides were differentially expressed in cats with sarcomeric gene mutations compared with cats without mutations. Results: Our results demonstrated characteristic protein expression in control cats, Maine Coon cats, and Maine Coon cats with gene mutations. In cats with gene mutations, peptide expression profiling showed an association with three peptides, Cytochrome 3a132 (CYP3A132), forkhead box O1 (FOXO1), and ArfGAP, with GTPase domains, ankyrin repeats, and PH domain 2 (AGAP2). Discussion: The serum peptidome of cats with mutations might provide supporting evidence for the dysregulation of metabolic and structural proteins. Genetic and peptidomics investigations may help elucidate the phenotypic variability of HCM and treatment targets to reduce morbidity and mortality of HCM in cats.